Advanced system demonstration for utilization of biomass as an energy source. Volume IV. Design drawings (Wheelabrator Cleanfuel Corp., Washington, DC (USA), 1980)
This volume contains design drawings for the biomass cogeneration plant to be built in Maine. The drawings show a considerable degree of detail, however, they are not to be considered released for construction. There has been no actual procurement of equipment, therefore equipment drawings certified by suppliers have not been included. (DMC)